A follow‐up study to explore factors associated with rapid kidney function decline and new‐onset kidney disease among Chinese elderly population. Issue 11 (18th September 2022) - Xiong, Juan; Zheng, Xujuan; Luo, Jingang; Luo, Xiaohua; Zhang, Yiqin; Xu, Liping; Wang, Yuxin
Abstract : Aim: To explore potential factors associated with rapid kidney function decline and new‐onset kidney disease among a Chinese elderly population, and to examine the relationships between baseline serum uric acid (SUA), longitudinal change in SUA and rapid estimated glomerular filtration rate (eGFR) decline over 5 years for this Chinese elderly population. Methods: A 5‐year follow‐up study was conducted from 2016 to 2020 in Xiamen City, China; and 2436 elderly people with normal kidney function at baseline was included. The multivariable logistic regressions were used to explore risk factors for rapid eGFR decline and new‐onset kidney disease. Results: The median age of subjects was 65 years, and 38.5% were men. These elderly people experienced a median 5‐year decrease in eGFR of 14.50 mL/min/1.73 m 2, and 11.2% of them had developed new‐onset kidney disease after 5‐year follow‐up. Participants with elevated SUA change from the normal group to the hyperuricemia group witnessed the highest decrease of eGFR after a 5‐year follow‐up than other groups. Multivariate analysis found advanced age, female, elevated baseline SUA, elevated SUA change, hypertension and triglyceride–glucose index were risk factors for rapid eGFR decline and new‐onset kidney disease. Conclusion: The Chinese elderly population was more likely to encounter rapid renal function decline and new‐onset kidney disease. A regular test for kidney disease was strongly recommended for these elderly people who were female, with advanced age, with elevated baseline SUA and elevated SUA change; and had high levels of insulin resistance, and blood pressure. The derived findings can offer significant evidence for targeted prevention for the Chinese elderly population. Geriatr Gerontol Int 2022; 22: 968–975 . Abstract :